Examination of the molecular relationships of sand frogs (Anura: Pyxicephalidae: Tomopterna) and resurrection of two species from the Horn of Africa - Zimkus, Breda M.; Larson, Joanna G. (Zootaxa, 2011)
Tomopterna kachowskii and T. elegans from Ethiopia and Somalia, both currently synonyms of T. cryptotis, are resurrected based on morphological and molecular data. Tomopterna hieroglyphica is determined to be conspecific with T. kachowskii, with the latter taking precedence. Analysis of mitochondrial 12S rRNA, t-valine, 16S rRNA data reveals that these species differ from each other by 7.7%, differ from other described species of the genus by at least 3.0% and are only distantly related to T. cryptotis. A phylogeny of the genus is constructed, and the relationships among species are discussed. Discriminant function analysis was completed using 25 morphological measurements to determine if the seven clades identified in molecular analyses have concordant morphological difference. Translations of the original descriptions are provided, and a detailed redescription of T. elegans is included as the original description was made with only juvenile specimens. Tomopterna kachowskii and T. elegans are distinguished from other species of sand frogs by their visible tympana, presence of an outer metatarsal tubercle and moderate pedal webbing. Slightly more extensive webbing and variable presence of a discontinuous row of small glands beneath the tympanum distinguishes T. elegans from T. kachowskii.